Navier Slip Condition on Time-Dependent Radiating Nanofluid with the Soret Effect - SUNEETHA, Sangapatnam; SUBBARAYUDU, Ketineni; WAHIDUNNISA, Lalahamed; POLU, Bala Anki Reddy (Engineering Transactions, 2020)
This work concentrates on the study of the two-dimensional hydromagnetic flow of nanofluids over an suddenly started nonlinear stretching sheet in the presence of radiation and dissipation. The Soret effect and heat generation are also taken into consideration. The transformed ordinary differential equations (ODEs) are solved numerically via the MATLAB RK4S approach bvp4c solver with the assistance of similarity variables. The effects of various parameters are explored and shown in graphs and tables. It is noted that the concentration increases as the Soret number increases within the boundary layer. An increase in velocity slip decreases the velocity and a reverse effect is observed for temperature. This model has significance in different areas such as polymer chemical and metallurgical industries, and other fields that use the latest technology and thermo-processed materials such as metallic and glass sheets.